Effect of alcoholic and cold aqueous extracts of Melia azedarch(L.) and Actellic insectiside in the second larval instars of Oryzaephilus surinamensis (Baghdad Science Journal, 2014)
The effect of alcoholic extract (2%,4%, 12%) and the fruits aqueous extract (12%,15%,25%,35%) of Melia azedarach and actellic insecticide of 0.01 concentration were tested on the second instar larvae ofOryzaephilus surinamensis .The obtained resuls were reveated that the highest kill ratio 80% at the concentration 12% of the alchoholic extract and 85% of the aqueous extract this was reflected effect abstracts on low rate of age adult emerging of larve treated and low productivity